Value creation and internationalization of Performing Arts: SEAM evaluation in flamenco festivals from 9 countries - Rastrollo-Horrillo, María Ángeles (My University, 2022)
This paper tells the story of a consulting research project in the International Association of Flamenco Festivals, with the aim of evaluating their role in the internationalization of flamenco and thus legitimizing their position in the performing arts (PAs) network. It would seem that the contribution of Flamenco Festivals (FFs) to the internationalization of flamenco companies is not known by other agents in the domestic network (artists, producers, or Spanish public administrations), nor has it been the subject of study in the literature. Using the Socio-Economic Approach to Management (SEAM), this research highlights the areas of value creation of these festivals, and their contribution to the internationalization of Spanish flamenco artists. Together with the organizers of festivals held in Spain and in 8 other countries, Spanish artists and producers are incorporated into the evaluation to generate a shared storytelling. The result shows that FFs have a central role in the creation of value (economic, social-cultural) by mobilizing PAs agents in origin and destination, helping to reduce the tensions that limit the creation of value in international markets. This research supports the important contribution of management consulting in the generation of useful and innovative knowledge with and for organizations.
Keywords: Flamenco (Folclore); Internationalization; Socio Economic Approach to Management -SEAM; Networks; Value creation; Flamenco festivals